2020
DOI: 10.4269/ajtmh.20-0231
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Differentiation of Opisthorchis-Like Eggs in Northern Thailand Using Stool Specimens Under National Strategic Plan to Control Liver Fluke Infection and Cholangiocarcinoma

Abstract: Liver fluke infection caused by Opisthorchis viverrini is recognized as a potential risk factor for cholangiocarcinoma (CCA). The National Strategic Plan to Control Liver Fluke Infection and Cholangiocarcinoma has implemented microscopic-based stool examination screening. However, eggs of O. viverrini and minute intestinal flukes (MIFs) are nearly morphologically similar and could result in inaccurate O. viverrini diagnosis. Stool specimens were collected from eight districts of Chiang Mai Province in northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…were more abundant than O. viverrini in the central part of Lao PDR [32]. In northern Thailand, using molecular diagnostics the occurrence of MIF was recently found to be 3.8-fold higher than O. viverrini [33].…”
Section: Discussionmentioning
confidence: 95%
“…were more abundant than O. viverrini in the central part of Lao PDR [32]. In northern Thailand, using molecular diagnostics the occurrence of MIF was recently found to be 3.8-fold higher than O. viverrini [33].…”
Section: Discussionmentioning
confidence: 95%
“…We explore the impact of imperfect diagnostic specificity on the observed prevalence under simplistic scenarios shown in figure 2 f ; in reality, we expect specificity for O. viverrini to covary with the endemicity of minute intestinal flukes. The increased use of molecular diagnostics enables the species of parasite egg to be identified [66], and recent improvements to O. viverrini antigen tests also provides a method to discriminate cases [67,68].…”
Section: Discussionmentioning
confidence: 99%
“…In areas of mixed infections with O. viverrini and MIF ( H. taichui , for example), molecular testing of the fecal eggs would be advantageous. Buathong et al (2020) 42 reported the usefulness of PCR and PCR-restriction fragment length polymorphism (PCR–RFLP) analysis targeting internal transcribed spacer 2 (ITS2) gene in differentially diagnosing O. viverrini and H. taichui infections in northern Thailand.…”
Section: Discussionmentioning
confidence: 99%